A streetcar named Desire - Kazan, Elia; Leigh, Vivien, 1913-1967; Brando, Marlon; Hunter, Kim, 1922-2002; North, Alex; Williams, Tennessee, 1911-1983 (Burbank, CA : Warner Home Video, 2012)
Follows the emotional disintegration of a Southern woman whose last chance for happiness is destroyed by her vindictive brother-in-law.
Based on the play by Tennessee Williams.
Originally released as a motion picture in 1951.
Features: forty-page book set that contains on-set/promotional photographs and film history trivia; commentary with Karl Malden, film historian Rudy Behlmer, and Jeff Young; Elia Kazan movie trailer gallery; movie and audio outtakes; Marlon Brando screen test; Elia Kazan: a director's journey documentary; five behind-the-scenes featurettes.
Director of photography, Harry Stradling Sr. ; editor, David Weisbart ; music, Alex North.
Vivien Leigh, Marlon Brando, Kim Hunter, Karl Malden.
MPAA rating: PG.
Keywords: Williams, Tennessee, -- 1911-1983 -- Film adaptations; Man-woman relationships -- Drama; Lust -- Drama; Sisters -- Drama; Fiction films; Based on the book; Feature films